Minat Beli Serum Bulu Mata melalui Media Sosial Instagram - Erfina Nurfitria Rifani; Ambarwati, Neneng Siti Silfi (Jurnal Tata Rias, 2021)
ABSTRACT ERFINA NURFITRIA RIFANI. Interest in Buying Eyelash Serum via Instagram Social Media. Jakarta. Diploma Three Makeup Study Program, Faculty of Engineering, Jakarta State University, 2021. This study aims to found out how interest in buying eyelash serum through social media for students of the D3 Makeup Program 2019 Jakarta State University. This research was made using quantitative descriptive methods by distributing questionnaires to students of the D3 Makeup program 2019 at Jakarta State University. Based on theoretical studies and data collection conducted in this study, itu produces 81,11%.